Does CEO compensation matter for eco-innovation? - Zhang, Xinyi (2022)
This study examines the effect of CEO compensation on environmental innovation (hereafter eco-innovation). Different types of CEO compensation are tested in this study, which are CEO total compensation, CEO long-term compensation and CEO short-term compensation. Utilizing a large sample of S&P 500(500 large companies listed on stock exchanges in the United States) for a period from 2010 to 2020, the results of this study reveal that CEO total compensation is positively associated with eco-innovation performance, and CEO long-term compensation is also positively associated with eco-innovation performance. Additionally, while prior literature mainly investigated how CEO compensation influences innovation and corporate social responsibility, this research focuses on the CEO compensation’s influence on eco-innovation which is rarely examined. Overall, this study contributes to the existing literature on the impact of CEO compensation and provides insights into the design of CEO compensation contracts.